2013
DOI: 10.1155/2013/841518
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure in Patients with Severe Falciparum Malaria: Using the WHO 2006 and RIFLE Criteria

Abstract: There are limited data on the application of the RIFLE criteria among patients with severe malaria. This retrospective study was conducted by reviewing 257 medical records of adult hospitalized patients with severe falciparum malaria at the Mae Sot General Hospital, Tak province in the northern part of Thailand. The aims of this study were to determine the incidence of acute renal failure (ARF) in patients with severe falciparum malaria and its association with RRT as well as in-hospital mortality. Using the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Higher propensity to contract malaria infection in men has been a consistent observation from this study region [9,20,34,35,38,39]. Male preponderance in malaria population has also been reported from other places in India [44−46] and elsewhere [47,48]. In contrast, female predominance was found in vivax malaria in Papua, Indonesia [36].…”
Section: Baseline Characteristicssupporting
confidence: 86%
“…Higher propensity to contract malaria infection in men has been a consistent observation from this study region [9,20,34,35,38,39]. Male preponderance in malaria population has also been reported from other places in India [44−46] and elsewhere [47,48]. In contrast, female predominance was found in vivax malaria in Papua, Indonesia [36].…”
Section: Baseline Characteristicssupporting
confidence: 86%
“…The low incidence of severe AKI compared to other studies can be explained by our inclusion of the full spectrum of hospitalized malaria patients and the predominance of P.vivax species [12]. The requirement of dialysis was similar to that of Thanachartwet et al [12], although lower than the reported 73–80% by other studies [6], [13], [15]. The 15.2% severe AKI mortality rate was in concordance with some studies, [4], [6] but lower than the range of 26–32% reported by others [10], [12].…”
Section: Discussionmentioning
confidence: 72%
“…Kidney injury, acute or chronic, is one of the common differential diagnosis of malaria manifesting as syndrome. The diverse presentations and aetiological mechanisms of AKI orbit around the properties of pRBC's on microcirculation, hypovolaemia, metabolic derangements or host immunologic responses to infection [175][176][177]. These major pathogenic features are originated by the Plasmodium infection but may not be limited by the annihilation of the infection.…”
Section: Malarial Acute Kidney Injury (Aki) and Oxidative Stressmentioning
confidence: 99%